The Relationship of Knowledge and the Use Of Personal Protective Equipment Among Farmer Users of Pesticides in Waru Village, Slogohimo District - Firmanda Rama Wisnu; Rezania Asyfiradayati (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Agriculture is one sector that has a big role in meeting people's food needs. One strategy used by farmers to increase food yields is to use pesticides to prevent pest attacks. However, in their use, farmers tend to pay less attention to the use of personal protective equipment to prevent the dangers of using pesticides. This research aims to determine the relationship between knowledge and the use of personal protective equipment among pesticide-using farmers in Waru Village, Slogohimo District. This research is quantitative with an observational descriptive design with a cross sectional approach. This research was conducted from September to November 2023. The research was carried out in Waru Village, Slogohimo District. The population in this study was 390. The research sample was 80 respondents. The sampling technique was carried out using a proportional sampling technique with inclusion and exclusion criteria determined by the researcher. Data collection was carried out using questionnaires and observation sheets. Data analysis uses descriptive univariate analysis, and bivariate analysis uses the chi-square test. The results of the research show that there is a significant relationship between knowledge and the use of personal protective equipment among pesticide-using farmers in Waru Village, Slogohimo District (p-value=0.045 <0.05); (OR=2,856; 95% CI = 1,126-7,240). Farmers with good knowledge about personal protective equipment have a 2.856 times chance of using complete personal protective equipment compared to respondents with low knowledge. It is hoped that community health centres and community health centres can educate farmers to increase their knowledge regarding using personal protective equipment to improve farmers' behaviour in using personal protective equipment when working.Keywords: Farmers, Knowledge, Occupational health safety, Pesticides, Personal protective equipment